‘God will protect us’: Belief in God/Higher Power’s ability to intervene and COVID-19 vaccine uptake - DiGregorio, Bernard D. (Review of religious research, 2022)
BackgroundVaccines represent one of the best ways to counter the COVID-19 pandemic. However, vaccine hesitancy among the population limits the effectiveness of vaccines. Recent research has explored the role of religion in vaccine hesitancy, but in doing so has encountered a "black box" problem. There is a relationship between religion and vaccine hesitancy, but the explanation for why remains unclear.PurposeThe purpose of this study is to explore the relationship between religion and vaccine hesitancy. We propose that how an individual conceptualizes God/a higher power is associated with getting vaccinated for COVID-19.MethodsWe use data from a nationally representative survey of U.S. adults, collected using the Amerispeak® probability-based panel via the National Opinion Research Center (NORC) at the University of Chicago. We examine the association between individuals’ views of God/a higher power as both a supervisory and an intervening figure on vaccine uptake and likelihood of getting vaccinated through logistic regressions.ResultsWe find that belief in God’s/a higher power’s supervision is not significantly associated with the odds of COVID-19 vaccine uptake or vaccination intent. However, belief in God’s/a higher power’s ability to intervene in the world is significantly and negatively associated with the odds of COVID-19 vaccine uptake and the odds of having received or planning to receive a COVID-19 vaccine. In addition, in models where belief in the ability of God/a higher power to intervene are included, Christian nationalism ceases to have a statistically significant association with intent to receive a COVID-19 vaccine.Conclusions and implications:These findings suggest that how individuals conceptualize God/a higher power is associated with their willingness to get the COVID-19 vaccine. Given this, those who see God/a higher power as more involved in the world may contribute to delays in achieving herd immunity. This information benefits those working on vaccination campaigns in understanding the beliefs of some of those who are most hesitant to get vaccinated. In addition, this intervention mechanism could also mediate other negative relationships between religion and other science and health-related concerns.